Fibrinolysis/Proteolysis Balance in Stable Angina Pectoris in Relation to Angiographic Findings - Páramo, J. A.; Orbe, J.; Fernández, J. (Thrombosis and Haemostasis, 2001)
The plasma fibrinolytic/proteolytic balance was assessed in 60 stable angina patients who underwent control coronary catheterization and the results were correlated with angiographic findings and control samples (n = 20). The concentrations of t-PA, PAI-1, collagenase (MMP-1), tissue inhibitor of MMP (TIMP-1), plasmin-antiplasmin (PAP) complexes and α2-macroglobulin (α2-M) were measured in plasma samples. The results showed a significant increase of PAP (p <0.001) and a reduction of α2-M (p <0.001) in the group of patients when compared to controls, indicating a degree of fibrinolysis/proteolysis activation. There was no correlation between the different parameters analyzed and the extent of angiographically proven atherosclerosis (one or more stenotic vessels), while the t-PA levels were significantly elevated (p <0.03) in patients with coronary stenosis ≥75% or occlusion. We conclude that there is a disturbance of the plasma fibrinolysis/ proteolysis in patients with stable angina not related to the extent of atherosclerosis. The t-PA levels may be a good marker for coronary occlusion in these patients.
Keywords: Fibrinolysis; proteolysis; coronary disease; t-PA